Readiness for influenza and COVID-19 vaccination in Germany: a comparative analysis - Schulz, Anja A.; Abt, Yvonne; von Oppen, Linus; Wirtz, Markus A. (Frontiers in Psychology, 2024)
Vaccination readiness refers to psychological motives and beliefs that decisively determine individual and collective vaccination prevention behavior. Readiness to get vaccinated depends on expected individual and social benefits and harms. Differences exist in the perception of the threat of a potential influenza vs. COVID-19 infection and its significance for the social environment. The aim of study was to compare the 7C components of vaccination readiness for influenza and COVID-19 vaccination in adulthood.Methods: N = 317 adults answered the 7C vaccination readiness scale in two vaccination specific versions (influenza vs. COVID-19) in an online survey from September 2022 to March 2023. Data were analyzed using repeated measures analysis of covariance, correlations and multiple regression.For COVID-19, there is a higher readiness to get vaccinated compared to influenza regarding Complacency-R (eta-p = .683), Constraints-R (eta-p = .684), Collective Rresponsibility (eta-p = .782) and Compliance (eta-p = .365). However, Confidence (eta-p = .161) and Conspiracy-R (eta-p = .256) indicate an enhanced readiness for influenza vaccination (interaction scales x vaccination type: eta-p = .602). Individual influenza vaccination recommendations and age do not or only marginally moderate these effects (interaction vaccination type x recommendation: eta-p = .155). The 7C subscales reveal a differentiated pattern of readiness for the two vaccination types. This emphasizes the relevance of the multidimensional structure of the construct vaccination readiness as well as the relevance of moderating effect of the respective vaccination type on the underlying motives and beliefs. Vaccination attitudes are influenced by cultural and social conditions as well as medical standards of care. Comparing attitudes to different vaccinations in different countries thus represents an important research desideratum in order to understand the concept of vaccination readiness more comprehensively..